HOUSEHOLDS’ PREFERENCE FOR SOME SELECTED COWPEA VARIETIES IN OYO STATE, NIGERIA - Ojedokun, Olajide (Journal on Processing and Energy in Agriculture, 2021)
This study was carried out to determine the factors influencing households’ preference for some selected cowpea varieties in Oyo State, Nigeria. Primary data were collected from a total of 250 households from five Local Government Areas (LGAs) using multistage sampling technique. Data were analysed using descriptive statistics and multinomial logit regression model. The study revealed that households mostly preferred the Oloyin variety of cowpea and that households mostly used Oloyin for their different cooking. Age of household head, primary occupation of household head, years of formal education, income, prices of cowpea varieties, aroma during cooking, ability to tolerate weevil infestation and absence of foreign particles influenced households’ preference for cowpea varieties. The study recommends that it is necessary for stakeholders and breeding institutions to give attention to the Oloyin variety if the Agricultural Promotion Policy’s aim will be achieved.
Keywords: Preference; Households; Cowpea; Varieties; Multinomial logit